User Innovation and Business Incubation - Carolin Eckinger; Mark W.J.L. Sanders (Utrecht University, Utrecht University School of Economics (U.S.E.), 2019)
This paper investigates user innovations in business incubation programs. User innovations are defined as innovations by users rather than suppliers of products, processes or services and have been identified as a potentially rich source of innovative ideas. Business incubators aim to help entrepreneurs find and develop ideas into viable businesses and have been shown to contribute to the success rate of start-ups. Current incubator acquisition strategies, however, are rather passive (founders need to apply) and selection into the incubation programs is geared towards attracting potentially profitable start-ups. User innovations often lack a dedicated founder team and the innovator typically has a lower ambition to build a venture and achieve profitability. In this paper we construct a measure based on existing literature to classify user innovations in a dataset of 296 start-ups that applied to one of two incubation programs between 2014 and 2017 in the Netherlands. Analysing this dataset, we found only 19 and find that incubator programs benefit user innovations as much as they do other ventures. Our data also suggests a negative self-selection bias of user innovations, shown by very few user innovations applying to incubation programs. At the same time only a few of the user innovations found have been selected for incubation, revealing an additional selection bias of incubator acquisition strategies towards user innovations
Keywords: 330; User Innovation; Business Incubation; Startups; Entrepreneurship